Tribocorrosion properties of AISI 1045 and AISI 2205 steels in seawater: Synergistic interactions of wear and corrosion - Beibei Zhang; Jianzhang Wang; Hao Liu; Yunfeng Yan; Pengfei Jiang; Fengyuan Yan (Friction)
Abstract Tribocorrosion denotes an irreversible material degradation for several metallic components used in corrosive environments, and it arises from the interplay between chemical, mechanical, and electrochemical processes. In this study, some investigation has been performed to compare the tribocorrosion behavior of AISI 1045 steel and AISI 2205 duplex stainless steel sliding against an alumina pin in seawater. The lowering in the open circuit potential (OCP) of AISI 2205 during the tribocorrosion demonstrates that its protective passive film was damaged by wear and resulted in a wear-accelerated corrosion in the wear track. However, sliding was found to accelerate the corrosion of the unworn areas for AISI 1045, leading to an anodic shift of the OCP. Moreover, the total material loss increased with an increase in the applied potential for both materials. It was revealed that AISI 1045 was more sensitive to corrosion under sliding than AISI 2205. Therefore, pure corrosion loss and corrosion-induced wear constituted the primary reasons for the degradation of AISI 1045 at applied anodic potentials.